MANAJEMEN PEMBELAJARAN STEM-PROBELEM BASED LEARNING BERBASIS LESSON STUDY DALAM KURIKULUM MERDEKA - Utaminingsih, Sri; Mahanita, Byarvega (Universitas Muria Kudus, 2024)
This research aimed to analyze learning management using a Science, Technology, Engineering, Mathematics-Model Problem Based Learning (STEM-PBL) approach based on Lesson study in science lessons, with a qualitative case study approach. Data sources were students, class teachers, colleagues, lecturers and school principals through observation, interviews and focus group discussions. The research resulted show that managing STEM-PBL learning began with the Plan stage by analyzing learning planning. Then the Do stage, observing the learning process in the open class: trigger questions to find problems, discussions to collect data to solve problems, and presentations. See stage, the results of the reflection were that learning management was student-centered but needed to be improved, namely smaller groupings of students with different genders, clear instructions, individual worksheets and presentations for all groups. It was concluded that learning management with STEM-PBL was effective in increasing student-centered learning activities. These findings provided valuable knowledge for educators and policy makers to improve the quality of learning through the STEM-PBL approach and Lesson study activities.